Karakterisasi Morfometri dan DNA Barcoding Keong Lola Merah (Rochia nilotica Linnaeus, 1767) dari Kepulauan Kei, Maluku - Triandiza, Teddy; Utami, Risnita Tri; Pesilette, Rosmi Nuslah (Universitas Diponegoro, 2024)
The lola snail (Rochia nilotica) is an herbivorous gastropod that lives in coral reef ecosystems. R. nilotica is an ecologically important species and has high economic value. This study aims to assess morphometric characterization and DNA barcoding. Analysis of growth patterns shows that red lola snails in the Kei Islands show an allometric growth pattern. Analysis of R. nilotica mitochondrial DNA (mtDNA) sequences resulted in 646 base pairs, containing 14 haplotypes with a total of 18 polymorphic sites. The results showed that the genetic diversity of R. nilotica populations in the Kei Islands was very high, namely nucleotide diversity (Pi) of 0.00460 and haplotype diversity (Hd) of 0.9457. The results of phylogenetic tree analysis showed five main clusters, namely four clusters of R. nilotica from the Kei Islands and one cluster of R. nilotica from Moorea Island and New Caledonia. The value of genetic distance between individuals and between R. nilotica populations is very low, namely 0.0026-0.0056 and 0.0034-0.0052. The results of the haplotype net analysis showed that there was haplotype mixing in all R. nilotica populations in the Kei Islands as indicated by the absence of a particular clade. Keong lola merah (Rochia nilotica) merupakan gastropoda herbivora yang hidup di ekosistem terumbu karang. R. nilotica merupakan spesies yang penting secara ekologis dan memiliki nilai ekonomi tinggi. Penelitian ini bertujuan untuk mengkaji karakterisasi morfometri dan DNA barcoding. Analisis pola pertumbuhan menunjukkan keong lola merah di Kepulauan Kei menunjukkan pola pertumbuhan alometrik. Analisis sekuens DNA mitokondria (mtDNA) R. nilotica menghasilkan 646 pasangan basa, yang mengandung 14 haplotipe dengan jumlah total 18 situs polimorfik. Hasil penelitian menunjukkan bahwa keragaman genetik populasi R. nilotica di Kepulauan Kei sangat tinggi, yaitu keragaman nukleotida (Pi) sebesar 0,00460 dan keragaman haplotipe (Hd) sebesar 0,9457. Hasil analisis pohon filogenetik menunjukkan lima kluster utama, yaitu empat kluster R. nilotica asal kepulauan Kei dan satu kluster R. nilotica asal Moorea Island dan New Caledonia. Nilai jarak genetik antar individu dan antara populasi R. nilotica sangat rendah yaitu 0,0026-0,0056 dan 0,0034-0,0052. Hasil analisis jaring haplotipe menunjukkan bahwa terjadi percampuran haplotipe pada seluruh populasi R. nilotica di Kepulauan Kei yang ditunjukkan dengan tidak adanya klade tertentu.